2008
DOI: 10.2140/jomms.2008.3.1521
|View full text |Cite
|
Sign up to set email alerts
|

Elastic solutions for an inclined transversely isotropic material due to three-dimensional point loads

Abstract: We present the elastic solutions for displacements and stresses due to three-dimensional point loads in a transversely isotropic material (rock), for which the transversely isotropic full planes are inclined with respect to the horizontal loading surface. The closed-form solutions are derived by applying an efficient method, the double Fourier transform, to obtain the integral expressions for displacements and stresses. Subsequently, the double inverse Fourier transform and residue calculus are utilized to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As can be seen from Figure 10a, the curve displayed a positive and negative stage. Obvious stress concentration is formed in the loading area, in which the value reached the peak stress, then it attenuates with the stress propagation along the X [46]. It is observed that with the increasing values of E1/E2, the magnitude of stress became bigger.…”
Section: The Effect Of E1/e2 On Stress Distributionmentioning
confidence: 95%
“…As can be seen from Figure 10a, the curve displayed a positive and negative stage. Obvious stress concentration is formed in the loading area, in which the value reached the peak stress, then it attenuates with the stress propagation along the X [46]. It is observed that with the increasing values of E1/E2, the magnitude of stress became bigger.…”
Section: The Effect Of E1/e2 On Stress Distributionmentioning
confidence: 95%
“…Effects of such anisotropy on displacements and stresses can be essential to the design of structures. Hu et al and Liao et al presented the elastic solutions induced by the point load in a transversely isotopic fullspace whose isotopic plane is inclined to the horizontal loading plane. These solutions show that the displacements and stresses in the inclined transversely isotropic rocks by a point load are quite different from those induced in the horizontal transversely isotropic rocks.…”
Section: Introductionmentioning
confidence: 99%